Determinan Kesejahteraan Petani Tanaman Pangan di Provinsi Jawa Barat - Samuel Fery Purba; Astrina Yulianti; Yudha Raphael; Husnul Khotimah (Institut Pertanian Bogor, 2024)
Every year, West Java Province becomes the third largest rice-producing province in Indonesia, with a production of 9.43 million tons in 2022. However, this condition is inversely proportional to the welfare of food crop farmers when viewed from the exchange rate of food crop farmers (NTPTP), which in the last two years has been below 100%. The purpose of this study is to evaluate the effect of rice crop production, rice crop productivity, the selling price of dry milled grain, production costs, and additional capital on NTPTP in West Java. Secondary data were obtained from the Central Bureau of Statistics and the Directorate General of Food Crops, Ministry of Agriculture, from 2010–2022. Multiple linear regression analysis is used to examine the determinants of the welfare of food crop farmers. The findings of this study show that the selling price of dry-milled grain has a significant effect on increasing NTPTP. In contrast, rice crop production, productivity, production costs, and capital increases are not. The selling price of dry-milled grain influences the welfare of food crop farmers in West Java. Government policymakers can use this study in the agricultural sector to overcome the high expenditure of farmers' production costs by providing subsidies on target and maintaining the cost of goods sold for rice for the welfare of farmers in West Java. Keywords: price of dry grain, exchange rate of food crop farmers, paddy production, paddy productivity, multiple linear regression